A giant condyloma accuminata - Rahman, MM; Khan, SA; Reza, E; Rashid, MM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):51-4. The abstract of this article is available on the PubMed website